2010
DOI: 10.1085/jgp.200910316
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Slo2.1 channels by niflumic acid

Abstract: Slo2.1 channels conduct an outwardly rectifying K+ current when activated by high [Na+]i. Here, we show that gating of these channels can also be activated by fenamates such as niflumic acid (NFA), even in the absence of intracellular Na+. In Xenopus oocytes injected with <10 ng cRNA, heterologously expressed human Slo2.1 current was negligible, but rapidly activated by extracellular application of NFA (EC50 = 2.1 mM) or flufenamic acid (EC50 = 1.4 mM). Slo2.1 channels activated by 1 mM NFA exhibited weak volt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
65
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(71 citation statements)
references
References 73 publications
6
65
0
Order By: Relevance
“…As reported previously (Dai et al, 2010), negligible currents were observed in oocytes injected with low amounts of KCNT2 cRNA under control conditions (Fig. 1A, top).…”
Section: Resultssupporting
confidence: 88%
See 4 more Smart Citations
“…As reported previously (Dai et al, 2010), negligible currents were observed in oocytes injected with low amounts of KCNT2 cRNA under control conditions (Fig. 1A, top).…”
Section: Resultssupporting
confidence: 88%
“…KCNT2 cDNA (provided by L. Kaczmarek, Yale University, New Haven, CT) was subcloned into the psGEM oocyte expression vector (Dai et al, 2010). A278R Slo2.1 was generated by using the QuikChange site-directed mutagenesis kit (Agilent Technologies, Santa Clara, CA) and confirmed by DNA sequencing.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations